Cysts of pleural origin: about an observation - Anavitarte, E; Arrutti, C; Añón, R (Cirugía del Uruguay, 2020)
A report is made of a case of aerial cystic formations in a girl aged 19 months, which, through and insufflation mechanism, developed respiratory insufficiency. Permanent cure was achieved by surgical procedures.